2008
DOI: 10.2174/157341208783497579
|View full text |Cite
|
Sign up to set email alerts
|

V. Amygdalina: Folk Medicine, Analysis, and Potential Application for Cancer Treatment

Abstract: Folk medicine (FM) is practiced by people without access to conventional medical services; it usually involves the use of natural remedies such as herbs or vegetable substances. Before the use of pharmaceutical drugs, and surgical procedures, these healing methods were used, and are still in use today. It is estimated that twenty five percent of all therapeutic drugs trace their origins to plants, and almost two-thirds of the people of the world rely on their healing powers. One hundred years ago, health care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…(Asteraceae) (VA) is a small shrub which is native to South Africa (Erasto et al, 2006;Izevbigie et al, 2008). VA is known as Ewuro and Etidot locally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Asteraceae) (VA) is a small shrub which is native to South Africa (Erasto et al, 2006;Izevbigie et al, 2008). VA is known as Ewuro and Etidot locally.…”
Section: Introductionmentioning
confidence: 99%
“…VA is well-known for its medicinal importance and it is used in Nigeria, Ghana, and South Africa for the treatment of diabetes (Akah and Ekekwe, 1995;Erasto et al, 2005). Its leaves are consumed either as vegetables (macerated in soup) or aqueous extracts as tonic for the treatment of various diseases (Izevbigie et al, 2008). Since 1992, a number of anti-diabetic studies both in vivo (Akah and Okafor, 1992;Nwanjo, 2005;Abraham, 2007;Ebong et al, 2008;Eteng et al, 2008) and in vitro (Erasto et al, 2009) have indicated VA to possess anti-diabetic property.…”
Section: Introductionmentioning
confidence: 99%